Desempenho de 79 progênies de soja na geração F6 e correlações fenotípicas, genotípicas e ambientais - Cunha, Marcela Cristina Garcia (2011)
Soybean farmers have interest on increasingly early highly productive cultivars has stimulated the development of new genotypes for breeding soy programs. So that, this study aimed to evaluate the agronomic characteristics of 79 progenies of ten biparental crosses Program Soybean Breeding in Federal University of Uberlândia. The experiment was conducted at the Capim Branco Farm, in the region of Uberlândia, MG, Brazil. Initially, hybridization occurred between the parents with desirable agronomic traits in the greenhouse. Afterwards, the selection was made by Bulk to the F4 generation. From this, we selected individuals in the F5 generation by Progeny Test, taking into account the tax yield and earliness. On February 10, 2010, it was held sowing conventional 79 progenies from ten biparental crosses to achieve the following characteristics: number of days to flowering (NDF), plant height at flowering (APF), color flower (CF), number of days to maturity (NDM), plant height at maturity (APM), height of first pod insertion (A1V), pubescence color (CP), type of growth (TC), cycle of progeny , lodging (AC), number of pods with 3 (NV3G), 2 (NV2G) and 1 (NV1G) grains, grain weight pro plan (PGP) and yield (PROD). Statistical analyzes were performed in the computer program in genetics and statistics GENES (Cruz, 2009). The population exhibited genetic variability, excepting two grains pod character, all characters showed significant differences. The highest values of heritability for the traits were number of days to flowering (78.49%) and yield (86.99%). The progenies UFUS 32, 02 UFUS, UFUS 01, 37 UFUS, UFUS 12, 36 UFUS, UFUS 16, 29 UFUS, UFUS 14 and 51 UFUS presented themselves as productive and genotypes with desirable agronomic traits such as plant height at flowering and maturity and type of indeterminate growth, to the conditions of Uberlândia-MG.The production component of the total number of pods per plant was positively correlated with the total number of pods of three grains.